Public Libraries in Foreign Countries: From Digital Gap to Digital Inclusion - G. V. Varganova (Библиосфера)
Information and communication technologies affect the library performance as a public good, intended to efficient and complete response to the social agenda of various socio-demographic population groups. The digital gap has an impact on a library within the framework of creation conditions for the social well-being of the population. The role of public libraries is increasing in reducing the digital gap, strengthening the material and technical base, technological infrastructure, identifying digitally disadvantaged groups of population that tend to use library computers and broadband Internet more frequently than those who are more advantaged. Attention is paid to digital inclusion which is considered to be the instrument for solving personal, social and professional needs of representatives of various population groups. The effectiveness of digital inclusion largely depends on the professional competencies of library professionals, on their ability to develop programs for library users to help them assess the digital readiness to enter the digital world. The network approach to training library professionals in digital literacy is characterized as the most flexible form that facilitates translation of positive experience to large groups of library specialists. The importance of partnership in promotion the necessity of digital literacy between public libraries with government authorities, universities, research centers and charitable foundations is stressed.